St. Patrick's Day - Gibbons, Gail (Gibbons, Gail. Explore the world with Gail Gibbons., 2023)
Who was St. Patrick? Why do we wear green on March 17th? Vetted by an expert, this new edition brings readers the most accurate and recent historical understanding of St. Patrick and the holiday celebrating him. Learn the story of Patrick's life, legends about the saint, and the history of the holiday. From shamrocks to shillelaghs, Gail Gibbons' signature combination of accessible text and clear, colorful illustrations creates a perfect introduction to the customs surrounding St. Patrick's Day-- parades, special meals, and of course wearing lots of green. Filled with facts, legends, and traditions, this book is ideal for kids learning about the holiday, Irish culture, and history.